PREFERENSI LOKASI INDUSTRI BERBASIS POTENSI LOKAL DI KABUPATEN BANYUMAS - Muhammad Abdullah Tsani; Prihadi Nugroho (Diponegoro University, 2019)
Locations for industrial development in Indonesia often determined by spatial allocation policies than the needs of industrial players. This creates a gap between the industrial spatial allocation stated in regulation and location needs of industrial actors. That indicated by the rejection of offerings location by industrial actors. The industry is a business activity and its location chosen in the most favourable place and influenced by the location factors. However, industrial location decisions not only emphasizes to the preferences of the perpetrators but also influenced by strategies and policies within the larger organizational environment of central and local governments. A quantitative approach used in this study to assess the location preferences of local-based industries (IBPL) in Banyumas Regency, Central Java Province, Indonesia. The objective is to evaluate the local spatial regulation of industrial allocation zones so that the gap can be reduced. The study findings revealed that IBPL site preferences related to the local content of industrial characteristics and industrial scales. Medium and large IBPLs indicated to clustered; their location preferences tend to close to the supplier industries and located in the main of roads. The spatial distribution of small-scales IBPL sites show the symptoms of spontaneous location. It influenced by factor of local potential accessibility of labor. There are ten location factors affecting IBPL site selection and lean to show the dependence element of traditional industry characteristics. The most influential location factors are accessibility to the local potencies and accessibility to the business networks.